(untitled) (Revista Espinhaço, 2019)
The Peruvian North Coast is one of the regions responsible for the emergence of monumental architecture in the South American continent, with a prominent remote socio-cultural and economic development in the third millennium of the preChristian era. In addition, very early, groups that occupied this region were responsible for major engineering works (such as irrigation by canals), enabling the vertiginous growth of agriculture capable of supporting large populations and, consequently, the emergence of technological complexity linked to production of textile, ceramics and metallurgy. All of this development is directly related to cosmologies, which not only justify but structure life in the Central Andes for millennia. This paper aims to present archaeological structures in Cerro Ventarrón, in the Lambayeque Valley, and how the study of physiographic characteristics, associated with the concepts of place and landscape, has helped to understand the way of life of the various groups that occupied the area over 5,000 years. For this, several field works were carried out in order to map, understand the implantation system and the cosmographic links of these archaeological structures, according to Andean thought. As a result, it was observed that the implementation of these structures is linked to regional sociogeographic frameworks, but associated with the common forms of thought and social organization shared by different societies of the Andean world.